Symbolic interactionist takes on music - Schneider, Christopher J.; Kotarba, Joseph A. (Bingley, U.K. : Emerald, 2016)
Participants from Couch-Stone Symposium 2014 have transformed their presentations into elegant papers for this collection. Chapters fall into three categorical themes, largely reflecting their position in the symposium but, more importantly, reflecting a natural progression in scope of symbolic interactionist work in music: moving from observations of the individual to observation of organizations to interdisciplinary observations of music from scholars in related disciplines.
Saved by rock 'n' roll: Lou Reed, his fans and the becoming of the (marginal) self / Thaddeus Muller -- Crews, camps and communities: place and belonging in jam festival scenes / Robert Gardner -- Feminizing a musical form: women's participation as barbershop singers / Jeffrey Nash, Dina Nash -- "When I feel a song in me<U+201d>: exploring emotions through the creative songwriting process / Maggie Cobb -- Negotiating fan identities in K-pop music culture / J. Patrick Williams -- Music videos on YouTube: exploring participatory culture on social media / Christopher Schneider -- Musical interactions: girls who like and use rap music for empowerment / Raphael Travis, Scott Bowman, Joshua Childs, Renee Villanueva -- The church and the streets: an ethnographic study of the Christian hip hop music scene in central Texas / Jonafa Banbury -- 'Are you in the pit?' role embracement among online rock fans / Andrea Baker -- Musical pastiche: the case of Matisyahu / Thaddeus Atzmon -- Music is rhythm, rhythm is life: the living moment / Eugene Halton.
Includes bibliographical references.
Print version record
Keywords: Social Science, Social Classes; Social interaction; Symbolic interactionism